2013
DOI: 10.1177/1078390313492173
|View full text |Cite
|
Sign up to set email alerts
|

In Search of an Adult Attachment Stress Provocation to Measure Effect on the Oxytocin System

Abstract: BACKGROUND Oxytocin is a promising biomarker for psychiatric conditions arising from early relational trauma, childhood maltreatment, and attachment dysregulation, including posttraumatic stress and dissociative disorders. OBJECTIVE This exploratory pilot study examined plasma oxytocin as a biomarker for alterations in the attachment system. DESIGN We used a single group, repeated-measures design with 15 women. The protocol used a film clip previously validated as a provocation to the hypothalamic–pituitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 51 publications
(63 reference statements)
2
23
0
Order By: Relevance
“…In contrast, a study carried out by this work group found pronounced OXT increases in schizophrenia patients, but not in healthy controls after exposure to children's movie scenes of attachment and loss [30]. Results of this study [30] also confirm that movie clips are a highly effective tool to elicit emotions and empathy in patients with schizophrenia as in other population [31], although few studies have examined the OXT response to emotional videos in non-clinical [32][33][34][35] or clinical populations [30] and show overall inconclusive results. In healthy women, a decrease of OXT after positive and unchanged OXT levels after negative emotions could be observed [32].…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…In contrast, a study carried out by this work group found pronounced OXT increases in schizophrenia patients, but not in healthy controls after exposure to children's movie scenes of attachment and loss [30]. Results of this study [30] also confirm that movie clips are a highly effective tool to elicit emotions and empathy in patients with schizophrenia as in other population [31], although few studies have examined the OXT response to emotional videos in non-clinical [32][33][34][35] or clinical populations [30] and show overall inconclusive results. In healthy women, a decrease of OXT after positive and unchanged OXT levels after negative emotions could be observed [32].…”
Section: Introductionsupporting
confidence: 51%
“…Furthermore, it is important to acknowledge that there is no established standard protocol in the measurement of OXT after viewing movie clips in German language. The experimental setup was based on the few other studies that have investigated OXT response to video-based or real-life stimuli [29,33,35]. Nonetheless, a systematic understanding of the physiological OXT response to emotional stimuli in healthy adults is still lacking, and it could be argued that introducing a new paradigm to compare patients with controls might lead to a reduced interpretability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin has also been shown to stimulate Cox-2, an enzyme that has been linked to an increased risk for cancer (Bakhle, 2001), in the uterine tissue of pregnant cows (Fuchs, Rust, & Fields, 1999). Evidence that oxytocin may be related to the etiology of mental health problems and disease comes from studies that show a correlation between circulating levels of oxytocin and symptoms of post-traumatic stress disorder and disassociation in humans Munro, et al, 2013). And, postmortem brain levels of oxytocin show that OT is substantially elevated in the hippocampus of individuals with Alzheimer's Disease (Mazurek, Flint, Beal, & Martin, 1987).…”
Section: Hormonal Influences On Stress Immune Function and Diseasementioning
confidence: 99%
“…A recent pilot study ( n = 14) used film clips of bonding or abandonment scenes to investigate OT plasma levels as a potential biomarker for alterations in the female attachment system. While lower OT plasma levels during abandonment scenes were positively correlated with posttraumatic stress symptoms, higher OT plasma levels during bonding scenes were negatively correlated with scores of dissociation and somatization ( Munro et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%